1990
DOI: 10.1113/jphysiol.1990.sp018147
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and dimensions of cardiac output changes in humans at the onset and at the end of moderate rhythmic exercise.

Abstract: SUMMARY1. An improved Doppler ultrasound technique was used to measure stroke volume (SV) and cardiac output (CO) on a beat-to-beat basis in a group of supine humans before, during and after periods of standardized, rhythmic exercise, involving the quadriceps muscle groups on both sides. The development of CO on such bouts of exercise was compared to Doppler ultrasound records of the simultaneous femoral arterial flow (FF) response.2. Records of CO at rest revealed spontaneous fluctuations around a mean level,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
45
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 26 publications
10
45
0
Order By: Relevance
“…The large increase in SV during squat would suggest that central blood volume translocation was already manifest during squatting. Others have demonstrated that SV is actually also maximized in the supine position due to central blood volume translocation, as evidenced by virtually no increase in SV with the onset of supine exercise (15). Despite this evidence, we cannot conclusively exclude the possibility that there could be some elevation in SV when standing up from supine, which might make the central hemodynamic environment evoked by rising from supine slightly different than rising from squat.…”
Section: Cardiopulmonary Baroreflex Does Not Explain Ioh On Rising Frmentioning
confidence: 52%
“…The large increase in SV during squat would suggest that central blood volume translocation was already manifest during squatting. Others have demonstrated that SV is actually also maximized in the supine position due to central blood volume translocation, as evidenced by virtually no increase in SV with the onset of supine exercise (15). Despite this evidence, we cannot conclusively exclude the possibility that there could be some elevation in SV when standing up from supine, which might make the central hemodynamic environment evoked by rising from supine slightly different than rising from squat.…”
Section: Cardiopulmonary Baroreflex Does Not Explain Ioh On Rising Frmentioning
confidence: 52%
“…Some authors, however, soon identified two components of the V O 2 kinetics: 1) a rapid, almost immediate phase (phase I) (5,54,55), which they attributed to an immediate increase in cardiac output (Q ) at exercise start; and 2) a subsequent slower phase (phase II), to which they restricted the influence of muscle metabolic adjustments. The strongest support to this view came from the demonstration that the kinetics of Q (12,13,16,60) and arterial O 2 flow (Q a O 2 ) (27) are very rapid.…”
mentioning
confidence: 85%
“…This view restricts the correspondence between lung O 2 uptake and muscle O 2 consumption to the monoexponential phase II. Perhaps the strongest piece of evidence in support of the phase I concept is the finding that the kinetics of cardiac output (Q ) upon light exercise onset is much faster than that of V O 2 (12,14,21,34,38,59,60). In fact, assuming invariant O 2 concentration in mixed venous blood in the first seconds of exercise, this finding would imply, according to the Fick principle, a corresponding rapid increase in V O 2 .…”
mentioning
confidence: 94%